Governance and implementation of the Emergency Department to Community (EDC) initiative to support complex care needs in Australia - Kanchan Marcus; Philip Haywood; Gabriela Uribe; Alison Austen; Marguritte Battye; Patrick Bolton; Miranda Shaw; Shannon Saad; Paul Esplin; Althea Barry; Jenny Cox; Lisa Parcsi; et al. (Leadership in Health Services, 2026)
Purpose This paper aims to qualitatively evaluate the nature and strength of partnerships examining the structural factors, including information sharing and policy alignment that support the transition of patients from emergency department presentations across New South Wales, Australia. Design/methodology/approach An evaluation using a qualitative design and analytical framework was undertaken. Documentary analysis and semi-structured interviews and focus groups were conducted with stakeholders, allied health professionals and community partners. Findings from these sources were triangulated and presented at a Roundtable to gather feedback and insights. Findings Emergency Department to Community (EDC) implementation reflects localised approaches; in a rural local health district (LHD), the initiative is transitioning towards a business-as-usual model, while in metropolitan Sydney LHD a formally designated virtual model is used. Yet all LHDs conduct most care coordination using telehealth modes with some face-face contact when required. Governance arrangements are effective across most sites, with implementation tailored to context. Cross sector collaborations and partnerships was a core feature of this initiative, while upstream barriers persist in primary care and regional disparities. Originality/value This study provides empirically original insights into how the EDC model of care is governed and implemented in four LHDs, with qualitative insights from key leaders at local districts, doctors, nurses, social workers, allied health professionals, hospital managers and not-for-profit providers. By addressing social determinants of health, such as housing and access to services, these models move beyond traditional service delivery to improve both health and social outcomes for those most at risk.